Interpersonal relationship, workload pressure, work environment and job stress level among culinary internship students/ Khairunnisa Mohamad Abdullah and Nor Rabiatul Adawiyah Nor Azam - Mohamad Abdullah, Khairunnisa; Nor Azam, Nor Rabiatul Adawiyah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
This study explores the influence of interpersonal relationship, workload pressure and work environment on job stress level among culinary internship students. A descriptive research design using a quantitative approach was used. A questionnaire-based survey was disseminated to 120 culinary students from several culinary institutions within the Klang Valley area who already finished or still undergo their internship program. The findings disclosed that interpersonal relationship, workload pressure and work environment significantly contributed to work stress among culinary internship students. Therefore, learning how to cope with pressure in a professional environment is critical to build in initial career to keep ahead in challenging environments. The culinary institutions should collaboratively work with the industry and monitor the students' work placement on a regular basis to ensure they obtain quality internship experiences that can positively impact the culinary career intentions after graduation.